A remarkable new genus and species of Hansenauropodidae (Myriapoda, Pauropoda) from the seashore of Hainan Island, China - Bu, Yun (Zootaxa, 2020)
Psammopauropus macrospinus gen. et sp. n., a remarkable new genus and species of the pauropod family Hansenauropodidae is described from the marine littoral habitat of Hainan Island, South China. It has one pair of dorsal spines on the pygidium differentiated from seta a1, large globular seta st on pygidium, and globular distal setae on the tarsi by which Psammopauropus can be easily distinguished from all other genera of the family. In addition, the adaptive characters of the littoral pauropods are preliminary discussed. This is the first record of the family Hansenauropodidae from China.